Moringa Leaf Nanoparticles as an Alternatives to Improve Hemoglobin and Hematocrit Levels in Stunting Toddlers - Gustiya, Sherly Dwi; Hadisaputro, Suharyo; Sumarni, Sri (Universitas Muhammadiyah Semarang, 2022)
Background: Stunting is a condition of short toddlers is a discrepancy between height for age which is measured based on the z-score <-2 SD. The highest prevalence of stunting in Central Java was in Magelang Districts by 37.6%. Aims: The objective of this study is to prove that consuming Moringa Oleifera leaf nanoparticles influences the increase in hemoglobin and hematocrit levels in stunting toddlers. Method: This is a quasy experimental study with pretest and posttest with control group design. The number of samples were 40 stunting toddlers who measured based on the z score <-2 SD. Those were divided into treatment groups (Moringa Oleifera leaf nanoparticles dose of 65 mg/day and supplementary feeding) and control groups (supplementary feeding) each group consisted from 20 toddlers. Interventions were given for 21 days. Examination of hemoglobin and hematocrit levels using the Hematology Analyzer method. Results: The hemoglobin level increased significantly from 11,365 g/dL to 12,610 g/dL with a value of p=0.001 in the intervention group. Moreover, hemoglobin level in the control group a slightly increased from 11.455 g/dL to 11.610 g/dL with a value of p=0.648. Hematocrit levels increased significantly (p=0.001) from 35.810% to 43.575% in the intervention group. Hematocrit level also improved slightly in the control group from 31.330% to 31.690%. However, it was not significantly with p=0.455. Conclusion: It is Proved that Moringa Oleifera leaf nanoparticles improves hemoglobin and hematocrit levels in stunting toddlers. The increase hemoglobin and hematocrit levels are greater in the intervention group rather than the control group.